Anthrenus (s. str.) corona (Coleoptera, Dermestidae, Anthrenini): a new species in the A. pimpinellae Fabricius, 1775 complex from Turkey - Holloway, Graham J. (Zootaxa, 2021)
A new species from Turkey, Anthrenus (s. str.) corona, belonging to the Anthrenus pimpinellae complex is presented. The species is described from a single specimen discovered in the collection held by the Natural History Museum, London. The species was uncovered during the dissection of many specimens for the purpose of curation. The species is compared in detail to A. goliath, the most likely confusion species. An obvious external feature of the specimen is its large size, putting it apart from nearly all other species within the complex. The parameres and median lobe are slim, differing in many ways from A. goliath.